The Relationship Between Price Perception and Service Quality Towards Repurchase Intention with Store Reputation as A Mediator: Study of Golden Boy Store - Sudarmo, Gesy Ayu Pramudita; Radianto, Wirawan Endro Dwi (Universitas Ciputra Surabaya, 2024)
This research aims to determine the role of reputation as a mediator in the relationship between the influence of price perception and service quality on repurchase intention at Golden Boy Store in Surabaya, which is a children's clothing wholesale shop. This research used a quantitative approach using a purposive sampling technique, with 207 samples in total which are calculated using SmartPLS 4. The results of the research showed that (1) price perception has no effect and not significant towards store reputation, (2) service quality has a significant effect towards store reputation, (3) price perception has no effect and not significant towards repurchase intention, (4) service quality has a negative significant effect towards repurchase intention, (5) store reputation has a significant effect on repurchase intention, (6) price perception has no effect and not significant on repurchase intention through store reputation, and (7) service quality has a significant effect on repurchase intention through store reputation